2020
DOI: 10.17511/ijpr.2020.i01.05
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of pediatric malignancy- A cancer hospital-based study

Abstract: Objective: Childhood malignancy being a significant cause of mortality among children. The aim of the study is to find out the epidemiology of tumours in children in our region below <14 years age who presented to tertiary care Cancer hospital, Bhopal, M.P. for period of four years (2015)(2016)(2017)(2018). Methodology: All children with cancer, aged 1-14 years diagnosed by mean of histological and cytological examination during a period of 4 years were reviewed. Results: During the period of four years 275 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…In a similar study conducted by Dasgupta et al 8 at a referral hospital in Kolkata, West Bengal, India, it was found that 49.39% were cases of hematological malignancies and the rest were nonhematological malignancies. ALL was the most common hematolymphoid malignancy (26.1%) and brain tumor (27.8%) was the most common solid tumor in our study population, which is also consistent with the study results reported by Gupta et al 7 wherein ALL constituted 44.3% of cases and brain tumor constituted 7.27% of cases. Dasgupta et al 8 in their study found that 25.08% of cases had ALL and among nonhematologic malignancies retinoblastoma was the most common tumor (10.62%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In a similar study conducted by Dasgupta et al 8 at a referral hospital in Kolkata, West Bengal, India, it was found that 49.39% were cases of hematological malignancies and the rest were nonhematological malignancies. ALL was the most common hematolymphoid malignancy (26.1%) and brain tumor (27.8%) was the most common solid tumor in our study population, which is also consistent with the study results reported by Gupta et al 7 wherein ALL constituted 44.3% of cases and brain tumor constituted 7.27% of cases. Dasgupta et al 8 in their study found that 25.08% of cases had ALL and among nonhematologic malignancies retinoblastoma was the most common tumor (10.62%).…”
Section: Discussionsupporting
confidence: 93%
“…7 Although the reason for this difference is not fully understood, it is thought that potential genetic and hormonal factors may be implicated in causing higher incidence among males. 7 Results of the present study depicted that 41.7% of the cases had hematolymphoid malignancy and 58.3% had solid tumors. In a similar study conducted by Dasgupta et al 8 at a referral hospital in Kolkata, West Bengal, India, it was found that 49.39% were cases of hematological malignancies and the rest were nonhematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations